1995
DOI: 10.1159/000159096
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced 5-HT<sub>2</sub> Receptor Mediated Contractions in Diabetic Rat Aorta: Participation of Ca<sup>2+</sup>Channels Associated with Protein Kinase C Activity

Abstract: The aim of this study was to determine how the contractile responses to 5-hydroxytryptamine (5-HT) are altered in aortas from rats with streptozotocin-induced diabetes and to explore the possible mechanisms of the altered vascular reactivity to 5-HT in diabetes. In the presence of extracellular Ca2+ (2.5 mM), the contractile responses to stimulation of 5-HT2 receptors with 5-HT were greater in aortas from diabetic rats as compared with those from age-matched controls. Similarly, phorbol-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
(27 reference statements)
5
13
0
Order By: Relevance
“…This finding supports previous reports using aorta and other vessels from diabetic animals [4][5][6][7][8]10]. Recently, we have demonstrated that the contractile response to 5-HT is also enhanced in diabetic rat aorta [19], It seems likely that the enhanced responsiveness of diabetic aorta to noradrenaline and 5-HT is due to a greater Ca2+ influx through Ca2+ channels as a consequence of increased PKC-activated process. First, the contractions induced by phorbol esters are greater in diabetic aortas compared to controls [12,19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding supports previous reports using aorta and other vessels from diabetic animals [4][5][6][7][8]10]. Recently, we have demonstrated that the contractile response to 5-HT is also enhanced in diabetic rat aorta [19], It seems likely that the enhanced responsiveness of diabetic aorta to noradrenaline and 5-HT is due to a greater Ca2+ influx through Ca2+ channels as a consequence of increased PKC-activated process. First, the contractions induced by phorbol esters are greater in diabetic aortas compared to controls [12,19].…”
Section: Discussionsupporting
confidence: 92%
“…rats. Diabetic rats also manifested other symptoms of the disease including polyuria, polydipsia and cataracts, as previously reported [19].…”
Section: General Features O F Animalssupporting
confidence: 83%
See 1 more Smart Citation
“…33 Ca 2ϩ causes muscle contraction. 34 We have confirmed that 5-HT 2A receptor mRNA is expressed in cultured human VSMCs by RT-PCR (data not shown). Using these cells, we revealed that 5-HT enhances IL-6 synthesis in VSMCs via the 5-HT 2A receptor.…”
Section: Discussionsupporting
confidence: 56%
“…The increased contractility to both agents in diabetes without any change in the sensitivity indicates an impairment in postreceptor events, other than an impairment in receptor activation. Enhanced 5-HT contractility in diabetic rat aorta has been reported to be a consequence of increased protein kinase C-activated processes [47]. It has been well reviewed that activation of protein kinase C pathway could lead to vascular dysfunction in diabetes and that high doses of vitamin E could decrease the enhanced diacylglycerol and protein kinase C activity in diabetic vasculature processes [48].…”
Section: Discussionmentioning
confidence: 99%